From satirical piece to commercial product: the mid-Victorian opera burlesque and its bourgeois audience - Cormac, Joanne (Tayor & Francis, 2017)
Current studies of burlesque position it as a subversive genre that questioned cultural and social hierarchies and spoke to diverse audiences. Central to this interpretation are burlesque’s juxtapositions of high and low culture, particularly popular and operatic music. This article problematizes this view, proposing that mid-Victorian burlesques lost their satirical bite. Demonstrating little concern for the tastes or interests of the poorer or the most elite members of the audience, they specifically targeted the bourgeoisie. The article places three mid-Victorian burlesques in the wider context of the commercial development of the West End post the 1851 Great Exhibition. It proposes that this broader context, and not the genre’s perceived social role, provides the key to understanding the impulses driving the musical choices. It argues that juxtapositions of ‘high’ and ‘low’ music were far from subversive, rather they were included for commercial reasons, offering variety, but variety within strict bourgeois limits.